Oxidation during electric arc spray forming of steel - Newbery, A; Grant, P (Elsevier, 2006)
Twin wire electric arc spraying is being developed as a technique to form thick steel deposits for rapid production tooling by robotically manipulating several arc guns over a ceramic pattern. Even though nitrogren atomising gas is used to spray the steel, entrainment of oxygen from the surrounding atmosphere of the large extraction booth results in deposits that are high in oxide and substantially lower in carbon than the original steel feedstock wire. The amount of oxidation and carbon loss can be reduced if spraying is carried out in a smaller, enclosed chamber. Under chamber spraying conditions, controlled additions of oxygen to the nitrogen atomising gas leads to an increase in deposition temperatures, better bonding with the substrate, a coarser microstructure, a decrease in deposit hardness and increased deposit brittleness through intersplat delamination and oxide cracking. Differences in substrate shape, gun manipulation and oxygen entry point into the spray between chamber and spraying in a booth using a robot also alters the balance of oxidation and carbon loss processes. Oxidation during the spraying of thick steel deposits can happen in three main ways: (1) primary droplets in-flight prior to deposition; (2) incorporation of secondary droplets generated by splashing; (3) at the deposit top surface.